1995
DOI: 10.1101/gr.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The human obese (OB) gene: RNA expression pattern and mapping on the physical, cytogenetic, and genetic maps of chromosome 7.

Abstract: The recently identified mouse obese (ob) gene apparently encodes a secreted protein that may function in the signaling pathway of adipose tissue. Mutations in the mouse ob gene are associated with the early development of gross obesity. A detailed knowledge concerning the RNA expression pattern and precise genomic location of the human homolog, the OB gene, would facilitate examination of the role of this gene in the inheritance of human obesity. Northern blot analysis revealed that OB RNA is present at a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 24 publications
3
124
0
8
Order By: Relevance
“…The placenta was found to express leptin mRNA at comparable or greater levels than adipose tissue. Green et al 21 using Northern blot analysis, also found leptin mRNA in polyAϩ RNA from placental tissue but at a lower level than in total RNA from adipose tissue. It is possible that a comparison of leptin expression from total RNA of fat tissue to that of polyAϩ RNA from placenta underestimated placental tissue as a major source of leptin production.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta was found to express leptin mRNA at comparable or greater levels than adipose tissue. Green et al 21 using Northern blot analysis, also found leptin mRNA in polyAϩ RNA from placental tissue but at a lower level than in total RNA from adipose tissue. It is possible that a comparison of leptin expression from total RNA of fat tissue to that of polyAϩ RNA from placenta underestimated placental tissue as a major source of leptin production.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, a product of Ob gene, is a newly discovered single-chain prohormone with the molecular mass of 16 kDa, which seems to play a key role in regulating body weight (1). Leptin is produced by various adipose tissues, although other tissues like fundus of the stomach, skeletal muscles, liver, placenta (2), heart (3), cumulus oophorus and granular cells of human ovary, mammary gland (4), and epithelial cells of the stomach (5) produce it too.…”
Section: Introductionmentioning
confidence: 99%
“…La localisation de son équivalent chez l'humain fut réalisée en 1995 (Green et al, 1995) et en se basant sur les observations faites sur les rongeurs, on posait l'hypothèse que l'obésité chez l'humain pouvait résulter d'une déficience relative ou complète en leptine. Par ailleurs, pour la majorité des sujets obèses, on est rapidement venu à la conclusion que le rôle de la leptine chez l'humain ne semblait pas aussi important que chez la souris.…”
Section: Formes Monogéniques D'obésitéunclassified